Labor costs and the adoption of robots in China - Fan, Haichao; Hu, Yichuan; Tang, Lixin (Journal of economic behavior & organization, 2021)
We study the effects of higher labor costs on the adoption of industrial robots by Chinese firms. We use the number of robots imported by firms from the customs data to measure the adoption of robots. To address endogeneity concerns, we focus on the effects of higher minimum wages from contiguous city pairs that straddle provincial borders. We find negligible effects of minimum wages on firms’ robot adoption over 2004–2007, but much larger and statistically significant effects over 2008–2012. For a 10% increase in the minimum wage over 2008–2012, the probability of a firm adopting robots increases by 0.11 percentage points, compared to an average adoption probability of 0.19% over the same period. The effects of higher minimum wages on robot adoption are stronger for firms with higher productivity, those in the coastal region, those with private ownership, and those from skilled-labor-intensive industries.